A new species and a new record of Psychotria (Rubiaceae) from Thailand - Srisuk, Teerawat; Chamchumroon, Voradol; Chantaranothai, Pranom; Pornpongrungrueng, Pimwadee (Thai Forest Bulletin (Botany), 2024)
A new species, Psychotria oxyalabastron, is described, and P. laui is newly recorded from Thailand. The description, distribution area, ecological information and taxonomic note are provided.